Effect of dietary zinc pectin oligosaccharides chelate on growth performance, enzyme activities, Zn accumulation, metallothionein concentration, and gene expression of Zn transporters in broiler chickens1. (11th February 2019) - Wang, Zhong Cheng; Yu, Hui Min; Xie, Jing Jing; Cui, Hu; Nie, Hao; Zhang, Tietao; Gao, Xiu Hua
Abstract: This study was to investigate the effect of zinc pectin oligosaccharides chelate (Zn-POS ) on growth performance, serum enzyme activities, tissue zinc accumulation, metallothionein (MT) concentrations, and gene expression of zinc transporters ( ZnT ) in broilers. Five hundred forty 1-d-old Arbor Acres broiler chicks were randomly assigned to 5 dietary groups with 6 replicates of 18 birds per replicate. The diets were formulated with the same supplemental Zn level (80 mg/kg diet) but different amount of the Zn-POS: 0, 200, 400, 600, and 800 mg Zn-POS/kg diet. ZnSO4 was used to adjust to the desired amount of the Zn (80 mg/kg) in the Zn-POS diets. Broilers were fed with the experimental diets for 42 d including the starter (days 1 to 21) and grower (days 22 to 42) phases. Our results showed that dietary supplementation of Zn-POS linearly and quadratically increased ( P < 0.05) the average daily gain and gain-to-feed ratio during 22 to 42 d and 1 to 42 d as well as body weight on day 42, whereas reduced ( P < 0.05) the sum of mortality and lag abnormalities in broilers on day 42. Besides, serum alkaline phosphatase and copper-zinc superoxide dismutase activities increased ( P < 0.05) linearly and quadratically in response to dietary Zn-POS supplemental level on day 42. Dietary Zn-POS supplementation increased Zn accumulation in serum (linear, P < 0.05), liver (linear, P < 0.05), and pancreas (linear and quadratic, P < 0.05). In addition, Zn-POS supplementation linearly and quadratically increased ( P < 0.01, P < 0.05, respectively) MT concentrations in liver and pancreas of broilers. Pancreatic mRNA levels of MT, ZnT-1, and ZnT-2 increased ( P < 0.05) linearly and quadratically, and the mRNA expression of metal response element-binding transcription factor-1 increased linearly ( P < 0.05), in response to dietary Zn-POS supplementation. In conclusion, supplementation of Zn-POS in the diet increases Zn enrichment in the metabolic organs such as liver and pancreas and promotes productive performance in broilers.